2021
DOI: 10.3390/ma14247813
|View full text |Cite
|
Sign up to set email alerts
|

Silver Conductive Threads-Based Embroidered Electrodes on Textiles as Moisture Sensors for Fluid Detection in Biomedical Applications

Abstract: Wearable sensors have become part of our daily life for health monitoring. The detection of moisture content is critical for many applications. In the present research, textile-based embroidered sensors were developed that can be integrated with a bandage for wound management purposes. The sensor comprised an interdigitated electrode embroidered on a cotton substrate with silver-tech 150 and HC 12 threads, respectively, that have silver coated continuous filaments and 100% polyamide with silver-plated yarn. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…When used as heaters embroidered to the facemask, the conductive threads are exposed to moisture and temperature changes. However, our recent study showed the suitability of conductive threads to be used as moisture sensors, with stable characteristics with moisture levels up to 50 μL of water, as well as artificial sweet and blood serum …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When used as heaters embroidered to the facemask, the conductive threads are exposed to moisture and temperature changes. However, our recent study showed the suitability of conductive threads to be used as moisture sensors, with stable characteristics with moisture levels up to 50 μL of water, as well as artificial sweet and blood serum …”
Section: Methodsmentioning
confidence: 99%
“…However, our recent study showed the suitability of conductive threads to be used as moisture sensors, with stable characteristics with moisture levels up to 50 μL of water, as well as artificial sweet and blood serum. 31 Because of the fact that embroidery strikes a delicate balance between the top and bottom thread tensions, the conditions and appropriateness of the needle, the tension of the backing fabric on the embroidery field, and the overall fabric stability, an allowable tolerance of approximately ±0.2 mm was applied to all dimensions, as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35] Previous studies demonstrated the embroidery process of conductive yarns or wires to work as sensors and data conductors. [36][37][38][39] However, further work is necessary to investigate the potentiality of producing graphene-based yarns in a scalable quantity, and then integrate such electroconductive yarns into fabrics as wearable biosensors via simple embroidery technique.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the single effect based on the change of resistance value, some sensors change the impedance value under the joint action of resistance and capacitance. As shown in Figure8b, Saima Qureshi et al137 used Silver-tech 150 to design a humidity sensor that can measure sweat. The sensor has an accuracy of 7.78 × 10 −7 mΩ −1 /μL and excellent washability.…”
mentioning
confidence: 99%